2017
DOI: 10.1159/000478784
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Dobesilate Is Protective against Inflammation and Oxidative/Nitrosative Stress in the Retina of a Type 1 Diabetic Rat Model

Abstract: Calcium dobesilate (CaD) has been prescribed to some patients in the early stages of diabetic retinopathy to delay its progression. We previously reported that the treatment of diabetic animals (4 weeks of diabetes) with CaD, during the last 10 days of diabetes, prevents blood-retinal barrier breakdown. Here, we aimed to investigate whether later treatment of diabetic rats with CaD would reverse inflammatory processes in the retina. Diabetes was induced with streptozotocin, and 6 weeks after diabetes onset, Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…There is an increasing body of evidence about the role of antioxidants in the control of diabetic retinopathy in animal models ( Table 2 ) [ 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , …”
Section: Animal Studiesmentioning
confidence: 99%
“…There is an increasing body of evidence about the role of antioxidants in the control of diabetic retinopathy in animal models ( Table 2 ) [ 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , …”
Section: Animal Studiesmentioning
confidence: 99%
“…In retinas of db/db mice (a model of type 2 diabetes) and in retinas of STZ rats, CaD significantly reduced biomarkers of oxidative stress and NF-κB activation with consequent decrease of pro-inflammatory cytokines, such as TNFα, IL-1β, IL-6, and IL-8 (Bogdanov et al, 2017; Voabil et al, 2017). In addition, in STZ rats, CaD reduced vascular leakage and VEGF expression (Rota et al, 2004).…”
Section: Antioxidantsmentioning
confidence: 99%
“…Notwithstanding, a few different clinical trials demonstrated enhancement in visual acuity after oral treatment. Diabetes increases tyrosine nitration in the retina, fundamentally in the ganglion cell layer, and treatment with CaD attenuates this increase in tyrosine nitration initiated by diabetes [122].…”
Section: Interplay Of Nitrosative Stress/oxidative Stress and Infmentioning
confidence: 99%